State formation in early medieval Castile: craft production and social complexity. (8th August 2017) - Grassi, Francesca; Quirós Castillo, Juan Antonio; Alonso Olazabal, Ainhoa; Ortega, Luis Angel; Fornacelli, Cristina
Abstract : The EARMEDCASTILE project, based at the University of the Basque Country, has received funding from the European Union's Horizon 2020 Research and Innovation Programme, Marie Sklodowska-Curie Action (grant agreement 656540);http://earmedcastile.blogspot.com ).